Hubungan Kelainan Letak Janin, Kehamilan Ganda dan Preeklamsia dengan Kejadian Ketuban Pecah Dini pada Ibu Bersalin di RSI Siti Khadijah Palembang Tahun 2021 - Ayu Ainun Khofifah; Helni Anggraini; Putu Lusita Nati Indriani (Universitas Batanghari Jambi, 2022)
Premature Rapture of Membranes is the rupture of the fetal membranes before the onset of labor. Based on world health Organization, the incidence of premature rapture of membranes is around 5-10% among all births. 1% of PROM happened during preterm pregnancy and 22% happened during aterm pregnancy. Based on Indonesian Nursing Diagnosis Standars (INDS). In 2016, the incidence of PROM in Indonesian was around 4,5% to 7,6% among all pregnancies. This study was aimed to find out whether there was a simultaneous correlation between fetal position, multiple pregnancy and preeclampsia with the incidence of premature rapture ofmembranes among maternity mothers at Siti Khadijah Palembang Islamic Hospital year 2021. This study applied survey analytical design using cross sectional approach. The population of this study was taken from all maternity mothers at Siti Khadijah Palembang Islamic hospital year 2021 with a total of 132 mothers. The total samples were 57 respondents who were taken by applying systematic random sampling method. The data were collected by using checklist. These data were then analysed using univariate and bivariare analysis with chi square statistics. It could be conclude that there was a correlation between fetal position (p value = 0,026) multiple pregnancy (p value = 0,026), and preeclamsia (p value = 0,030) with the incidence of Premature Rapture of Membranes among maternity mothers. It is expected that the result of this study be able to be used as a description for the hospital in order to improve the health service especially when dealing with pregnant mothers who experienced premature rapture of membranes.